2011
DOI: 10.1007/s11069-011-9849-x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of coastal and inland fatalities in landfalling US hurricanes

Abstract: Improvements in hurricane forecasts allowing for more timely evacuations from storm-surge zones are credited with reducing lethality of US landfalling hurricanes. The deadly reach of a hurricane, however, is not limited to storm-surge zones. About 80% of direct US hurricane fatalities since 1970 occurred outside of landfall counties, with most of these fatalities caused by inland flooding. We construct a geographic information system database combining the location and cause of fatalities, estimated wind speed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 27 publications
2
51
0
Order By: Relevance
“…The active season of 2005, with Katrina, Rita, and Wilma, demonstrated that hurricanes can inflict vast amounts of damage, and the need for hurricane research and preparedness has escalated (USGS 2005). The principal hurricane hazards causing these extreme losses are the violent winds and widespread inundation from storm surges and heavy rainfall (Czajkowski, Simmons, and Sutter 2011). This study focuses on the combined risk of high winds and storm surge at a location on the U.S. Gulf Coast.…”
mentioning
confidence: 99%
“…The active season of 2005, with Katrina, Rita, and Wilma, demonstrated that hurricanes can inflict vast amounts of damage, and the need for hurricane research and preparedness has escalated (USGS 2005). The principal hurricane hazards causing these extreme losses are the violent winds and widespread inundation from storm surges and heavy rainfall (Czajkowski, Simmons, and Sutter 2011). This study focuses on the combined risk of high winds and storm surge at a location on the U.S. Gulf Coast.…”
mentioning
confidence: 99%
“…Gaussian models assume that the variance is constant. Count models are based on the probability distributions appropriate to count data, e.g., Poisson and negative binomial, for which the variance increases with the mean (3,4). The negative binomial model is commonly used to adjust for overdispersion when modeling count data such as hurricane deaths (4), as in our data, and was used to construct a well-fitted model (1).…”
mentioning
confidence: 99%
“…It is well established that >50% of US deaths by tropical cyclones occur inland (4,5). A total of 89% of Hurricane Floyd's 56 deaths were from inland flooding (1999).…”
mentioning
confidence: 99%
“…Czajkowski et al (2011) show that the total rainfall and predicted fatalities have an exponential relation, with fatalities starting to occur in areas with more than 5 inches total rainfall (Figure 5.10). Figure 5.11 shows the total rainfall for hurricane Rita.…”
Section: Total Rainfall Mapmentioning
confidence: 96%
“…The literature review (Chapter 2) revealed that none of the current scales and indexes consider rainfall. The absence of rainfall was identified as a major issue based on data showing that a considerable part of tropical cyclone damage and death toll arise from rainfall (Rappaport, 2014, Czajkowski et al, 2011, Rappaport, 2000.…”
Section: New Tropical Cyclone Hazard Indexmentioning
confidence: 99%